La transversalidad de género como innovación política de gobierno / The Transversality of Gender as Political Innovation of Government - Levin, Silvia (Impacto Científico, 2020)
RESUMEN Se describe el enfoque que instalan las políticas transversales de igualdad de género como estrategias públicas de gobernanza, y las connotaciones innovadoras que trasladan a las relaciones entre Estado y sociedad y entre ciudadanos y ciudadanas en Argentina en el marco de América Latina. ABSTRACT This paper describes the approach installed by the transversal politics of equality of gender as public strategies of governance and the ninnovative connotations that translate the relationships between the State and society and between citizens in Argentina in the Latin American context